Proses Berpikir Metafora dalam Menyelesaikan Masalah Matematis Soal HOTS Berdasarkan Kemampuan Kognitif Siswa - Anas Ma'ruf Annizar; Fina Syahida Zahro (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
To improve students' critical thinking skills in solving High Order Thinking Skill (HOTS) questions, the ability to think metaphorically in learning is required. Thus, this study aimed to describe the metaphorical thinking process of students in solving HOTS mathematical problems by PISA approach. In this study, the research method was descriptive with a qualitative approach. The sampling technique was purposive sampling technique, which was a sampling technique suitable for this study. The results showed that based on the works of the three subjects, they had distinct characteristics in solving the problems. S1 who was classified in high category had a metaphorical form by looking at the room from the top side and based on the indicators, S1 had met the metaphorical thinking indicators. S2 who was classified in low category still did not have metaphorical form as compared to the indicators of identifying problems. However, S2 also had gone through metaphorical thinking process when compared to the indicators of connecting and deciding the main concept, as well as was able to illustrate ideas. Meanwhile, S3 who was classified in the middle category had a metaphorical form by only looking at the room side. S3 also had met several indicators of metaphorical thinking.